The Effect of Family Development Session through Family Hope Program on Visit to Integrated Healthcare Center and Child Nutritional Status: A Multilevel Evidence - Nisaus Zakiyah; Endang Sutisna Sulaeman; Eti Poncorini Pamungkasari (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: The Family Development Session through the Family Hope Program (FHP) uses the nutritional status of toddlers as an indicator of the quality of life that reflects the welfare of the community. This study aimed to analyze the effect of the Family Development Session (FDS) through the Family Hope Program on the child nutritional status.Subjects and Method: This was an analytic observational study with a retrospective cohort design. This study was conducted in Ponorogo, East Java, from December to February 2020. A sample of 200 children was selected by simple random sampling. The dependent variable was child nutritional status. The independent variables were FDS (FHP), maternal education, family income, social support, maternal knowledge, self-efficacy, complementary food, integrated community health center. The data were collected by questionnaire and analyzed by a multiple multilevel logistic regression.Results: Child nutritional status was positively associated with FDS (b= 1.24; 95% CI= 0.26 to 2.22; p= 0.014), high maternal education (b= 1.18; 95% CI= 0.16 to 2.19; p= 0.023), family income (b= 1.11; 95% CI= 0.11 to 2.11; p= 0.030), social support (b= 1.57; 95% CI= 0.46 to 2.67; p= 0.006), maternal knowledge (b= 1.24; 95% CI= 0.26 to 2.23; p=0.013), self efficacy (b= 1.38; 95% CI= 0.32 to 2.44; p= 0.011), complementary feeding (b= 1.35; 95% CI= 0.33 to 2.37; p= 0.010), and regular visit to integrated community health center (b=1.42; 95% CI= 0.28 to 2.56; p=0.015). Integrated health center had strong contextual effects on the child nutritional status with intra-class correlation (ICC) = 33.97%.Conclusion: Child nutritional status is positively associated with FDS, high maternal education, family income, social support, maternal knowledge, self efficacy, complementary feeding, and regular visit to integrated community health center. Integrated health center has strong contextual effects on the child nutritional status.Keywords: child nutritional status, integrated healthcare centerCorrespondence: Nisaus Zakiyah. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email:nizakiyaah@gmail.com. Mobile: +6285235948995.Journal of Health Policy and Management (2020), 05(03): 224-234https://doi.org/10.26911/thejhpm.2020.05.03.08